1991
DOI: 10.1002/ijc.2910470115
|View full text |Cite
|
Sign up to set email alerts
|

Counteraction of estradiol‐induced activation of tissue‐type plasminogen activator in a human breast cancer cell line by an anti‐estrogen, LY117018

Abstract: LY117018 is a non-steroid anti-estrogen which exhibits about 100 times higher affinity for estrogen receptor than tamoxifen, another anti-estrogen. The cell line ES-1, which was isolated from human breast cancer MCF-7 cells, was highly sensitive to the cytocidal action of estradiol. Growth of ES-1 cells was inhibited by 10(-8)M 17 beta-estradiol, a concentration that stimulated the growth of parental MCF-7 cells. The estradiol-induced growth inhibition of ES-1 cells was almost completely reversed by treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We used an E 2 -depleted culture condition to examine whether the addition of E 2 to the five breast cancer cell lines tested in this experiment promoted E 2 -dependent growth. Previous studies have shown that the growth of human breast cancer cell lines depends on the presence of 10 À8 to 10 À9 mol/L E 2 in the culture medium (23,24). Of the five cell lines, the addition of 10 À8 mol/L E 2 enhanced growth in the ER-a-positive cell lines (T47D, MCF-7, and R-27).…”
Section: Resultsmentioning
confidence: 92%
“…We used an E 2 -depleted culture condition to examine whether the addition of E 2 to the five breast cancer cell lines tested in this experiment promoted E 2 -dependent growth. Previous studies have shown that the growth of human breast cancer cell lines depends on the presence of 10 À8 to 10 À9 mol/L E 2 in the culture medium (23,24). Of the five cell lines, the addition of 10 À8 mol/L E 2 enhanced growth in the ER-a-positive cell lines (T47D, MCF-7, and R-27).…”
Section: Resultsmentioning
confidence: 92%
“…This may be related to the fact that t-PA is an estrogen-inducible enzyme and that is present when the total PA activity is high (Dickermann et al, 1989;Mizoguchi et al, 1990;Uchiumi et al, 1991;Yamashita et al, 1992). The presence of the ER itself in breast cancer is generally thought to be associated with a good prognosis (Foekens et al, 1989), although in our study the prognostic value of ER (P = 0.075) and PgR (P = 0.06) only approached significance (Table IV).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then cultured for 24 hr in RPMI 1640 methioninefree medium containing no serum (2 mlidish), and pulsed for 4 hr with 35S methionine (50 p Ciiml). The labelled, conditioned medium was collected and used for the experiments on EGF-inducible protein secretion or stored at -20°C as described previously (Mizoguchi et al, 1990;Uchiumi et al, 1991). The labelled, conditioned medium was mixed with a % volume of buffer containing 12.5% P-mercaptoethanol, 5% SDS, 25% glycerol and 0 .…”
Section: Polyaciylamide Gel Electrophoresis (Page) Of Protein Secretementioning
confidence: 99%
“…Northern blot analysis was performed as described previously (Mizoguchi et al, 1990;Mawatari et al, 1991;Uchiumi et al, 1991). Total cellular RNA was isolated from tumors or IMC cells incubated with or without EGF.…”
Section: Northern Blot Analysismentioning
confidence: 99%